Gastrointestinal endoscopy in the cat: Diagnostics and therapeutics. Issue 11 (November 2013) - Neiger, Reto; Robertson, Elise; Stengel, Christiane
Practical relevance: Endoscopic examination of the feline gastrointestinal (GI) tract is a minimally invasive method for obtaining biopsy samples of the GI mucosa, which is often necessary for a diagnosis of chronic GI diseases. In addition endoscopy has several therapeutic indications including foreign body retrieval, oesophageal stricture dilation and placement of a percutaneous gastrostomy tube. Clinical challenges: Initially, practitioners must learn the subtle manipulations necessary to efficiently guide the endoscope through the GI tract to obtain biopsy samples of high diagnostic quality, and develop skills for implementing interventional procedures (eg, foreign body removal). Another challenge in mastering GI endoscopy is the ability to recognise normal from abnormal, which requires many years of practice and experience. Endoscopy is a diagnostic and interventional procedure that should be performed only in conjunction with a thorough history, physical examination, appropriate laboratory evaluation, and radiographic and/or ultrasonographic imaging. Audience: This review is intended to familiarize both the general and referral practitioner with GI endoscopy as a minimally invasive diagnostic and therapeutic intervention for the feline patient. Evidence base: The guidance contained within this article is based on a combination of the published literature, the authors' personal experience and the experience of colleagues.